Temperature dependent structural evolution in liquid Ag50Ga50 alloy. (29th November 2017) - Su, Y; Wang, X D; Yu, Q; Cao, Q P; Ruett, U; Zhang, D X; Jiang, J Z
Abstract: The temperature dependence of atomic structural evolution in liquid Ag50 Ga50 alloy has been studied using an in situ high energy x-ray diffraction (XRD) experiment combined with first-principles molecular dynamics (FPMD) simulations. The experimental data show a reversible structural crossover at the temperature of about 1050 K. Changes in both electrical resistivity and absolute thermoelectric power at about 1100 K strongly support the XRD results. Additionally, FPMD simulations reveal the abnormal temperature dependent behavior of partial coordination number and atomic diffusivity at about 1200 K, elucidating that the partition experimentally observed changes in structure and properties could be linked with the repartition between Ag and Ga atoms in the liquid at around 1050–1200 K. This finding will trigger more studies on the structural evolution of noble-polyvalent metals in particular and metallic liquids in general.